Ideology in Noun Phrases: Quran expert says nonmarital sex is allowed in Islam - Bushamidi; Sawirman; Lindawati (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2022)
This research is analysis of noun phrases (NPs) to find the deepest meaning, namely ideological reference that indicates speakerâ€™s interest and purposes. In addition to being based on an integrated approach between analysis of form and function, the study departs from the insights that the statements about language is never only about language, and also it is never merely about statements. The research was conducted as a qualitative descriptive study. Therefore, the substance aspect of data is written language, namely a news report entitled â€œQuran expert says nonmarital sex is allowed in Islamâ€. The source of data was downloaded from www.thejakartapost.com. The term of population and sampel adheres to the information rich paradigm, so that the population is the entire clauses and the complement of preposition, while the samples are all NPs. The data collection was carried out by observational method, while the data collection technique was handled by reading and taking note. Method and technique of data analysis were operated through a layered model of NP structure that is proposed by Rijkhoff. In addition, NP classification related to ideological reference borrowed the Key Lingual Symbols (KLS) and ideology concepts that are extracted by Sawirman. Based on the analyzing of all data, this research found five key NPs that contain the spirit of discourse and represent the overall message that is conveyed by the author. Moreover, that five key NPs indicate the ideology reference, namely; the institutionalization ideology, the conflictual ideology, the praxis ideology, and the secondary ideology.